Preliminary characterization of the rio claro aquifer in Paulínia/SP - Teramoto, Elias Hideo [UNESP]; Kiang, Chang Hung [UNESP]; Chang, Maria Rita Caetano [UNESP] (My University, 2020)
This work presents the results of a systematic work for the characterization of the Rio Claro aquifer in the industrial district of Paulinia municipality. In this research, was performed the characterization of the geological framework and the hydraulic conductivity of aquifer. The results point to an aquifer composed of rocks deposited in a meandering fluvial environment, with the predominance of flood plain facies associated with channel facies distributed along narrow and relatively continuous belts. The hydraulic conductivity values vary four orders of magnitude, covering a range from 10-8 to 10-4 m/s, that is related to the lithological heterogeneity of the aquifer.
Caracterização preliminar do aquífero rio claro em Paulínia/SP
Keywords: Cenozoic deposits; Geostatistic; Rio claro aquifer; Shallow aquifers